Gender-Affirming Surgery in Persons with Gender Dysphoria. Issue 3 (March 2018) - Weissler, Jason M.; Chang, Brian L.; Carney, Martin J.; Rengifo, David; Messa, Charles A.; Sarwer, David B.; Percec, Ivona
Abstract : Summary: The landscape of gender dysphoria has changed dramatically in recent years secondary to increased societal acceptance, legislative changes, and medical providers' increased awareness of the associated psychosocial burden associated with the diagnosis. National and global advocacy efforts, in conjunction with expanded third-party insurance coverage, have resulted in new health care opportunities for patients suffering from gender dysphoria. Delivering quality, streamlined health care to these patients requires a complex multidisciplinary approach, involving multiple medical and mental health disciplines, including plastic surgeons. To accommodate the expanding demand for gender-affirmation surgery, academic medical centers specializing in these procedures are gradually emerging. Advancing surgical techniques in the setting of rising patient demand encourage plastic surgeons to increasingly provide high-quality health care to this diverse patient population in an effort to optimize psychosocial functioning and minimize the burden of gender dysphoria. Although the current literature is replete with the evolving surgical and technical approaches to gender-affirming surgery, there remain critical gaps in the plastic surgery literature describing the delivery of comprehensive care to these patients. To address these gaps, the authors establish a framework that plastic surgeons can use to guide their management of patients with gender dysphoria to optimize surgical and psychosocial outcomes. First, the authors describe a timeline of events that have shaped present-day transgender medicine and characterize the current role of the plastic surgeon in the management of gender dysphoria. Subsequently, the authors discuss psychosocial and ethical considerations surrounding gender dysphoria. Finally, the authors discuss the future scope of transgender medicine.